Inovasi Berdasarkan Motif Tenun Gringsing di Desa Tenganan Pegringsingan dalam Bentuk Fashion - Rizqia, Muhamad Rifki; Puspita, Ade Ayu; Damayanti, Anandhita Alvina (ATRAT: Jurnal Seni Rupa, 2023)
This study aims to develop an innovation of Gringsing weaving motifs in Tenganan Pegringsingan Village, Bali in dealing with economic activities in the midst of the COVID-19 pandemic and to find out the various types of Gringsing weaving motifs. The location of this research was conducted in Tenganan Pegringsingan Village, Manggis District, Karangasem Regency, Bali, on the grounds that the Gringsing weaving motif is the result of the cultural creativity of the Tenganan Village community traditionally based on Hindu religious beliefs, with conditions for philosophical values and meanings, and has a unique culture with technical techniques. manufacture of single ikat and double ikat as Indonesian cultural identity. This research is a qualitative research with the research and development stage is carried out using research and development Research and Development (R&D). Research and development aims to produce new products through the development process, but does not eliminate the identity of the Gringsing motif. This research emphasizes according to a certain sample and Saussure’s semiotic theory approach. Keywords: Gringsing weaving motif, tradition, culture ------------------------------------------------------------------------------------ Penelitian ini bertujuan untuk mengembangkan inovasi motif tenun Gringsing di Desa Tenganan Pegringsingan Bali dalam menghadapi kegiatan perekonomian di tengah pandemi COVID-19 dan mengetahui berbagai jenis motif tenun Gringsing. Lokasi penelitian ini dilakukan di Desa Tenganan Pegringsingan, Kecamatan Manggis, Kabupaten Karangasem, Bali, dengan alasan motif tenun Gringsing merupakan hasil kreatifitas budaya masyarakat Desa Tenganan secara tradisi berdasarkan kepercayaan agama Hindu, dengan syarat akan nilai dan makna filosofi, serta memiliki keunikan budaya dengan teknik pembuatan single ikat dan double ikat sebagai identitas budaya Indonesia. Penelitian ini merupakan penelitian kualitatif dengan tahap penelitian dan pengembangan ini dilakukan dengan menggunakan penelitian pengembangan Research and Development (R&D). Penelitian dan pengembangan bertujuan untuk menghasilkan produk baru melalui proses pengembangan, tetapi tidak menghilangkan identitas jenis motif Gringsing. Penelitian ini menekankan menurut sampel tertentu serta pendekatan teori semiotik Saussure. Kata kunci: motif tenun Gringsing, tradisi, budaya